Citizen-Centered Governance: The Mayor's Office of New Urban Mechanics and the Evolution of CRM in Boston - Crawford, Susan P.; Walters, Dana (Social Science Research Network, 2013)
Over the last three years, the Boston Mayor's Office of New Urban Mech anics, the innovative, collaborative ethos within City Hall fostered b y Mayor Menino and h